2020
DOI: 10.3390/cancers12061639
|View full text |Cite
|
Sign up to set email alerts
|

Results of a Phase I-II Study on Laser Therapy for Vaginal Side Effects after Radiotherapy for Cancer of Uterine Cervix or Endometrium

Abstract: Women who have previously received radiotherapy (RT) for gynecologic cancer often suffer from vaginal fibrosis and stenosis. The success of “non-ablative” laser therapy for postmenopausal vaginal atrophy has led to the idea of testing the laser in patients submitted to RT. In this prospective observational study, we selected patients who underwent pelvic RT followed by vaginal laser treatment. We scheduled three treatment sessions (at T0–T1–T2) and three controls (at T1–T2–T3) one month apart. The follow-up (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…Intravaginal laser therapy is a novel non-pharmacological technique, which alleviates symptoms associated with menopausal genital atrophy [ 60 ]. Perrone et al [ 61 ] reported a progressive increase in vaginal length following intravaginal non-ablative CO 2 laser comparing to baseline. Furthermore, to reduce the radiation related vaginal stenosis, vaginal dilators might be recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Intravaginal laser therapy is a novel non-pharmacological technique, which alleviates symptoms associated with menopausal genital atrophy [ 60 ]. Perrone et al [ 61 ] reported a progressive increase in vaginal length following intravaginal non-ablative CO 2 laser comparing to baseline. Furthermore, to reduce the radiation related vaginal stenosis, vaginal dilators might be recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Besides physiological changes, the unfavorable effect of radiation used to treat cervical cancer also influences vaginal health [ 33 , 34 ]. The use of laser treatment to revert the adverse effect of radical surgeries or radiotherapy for gynecological malignancy is also under active investigation [ 35 ]. The number of publications still rising, although the FDA has not approved vaginal laser treatment for those indications.…”
Section: Discussionmentioning
confidence: 99%
“…Perrone et al [40] conducted a prospective cohort study in which (N=43) patients suffering from vaginal shorting, atrophy, and stenosis following radiation therapy for gynecologic cancers received treatment with CO 2 laser therapy which showed improvement in vaginal length and VHI [40]. Moreover, Pieralli et al [7] reported in a prospective cohort study improvement in VHI and VAS in patients (N=50) with a history of breast cancer and with resultant oncologic menopause following treatment with vaginal CO 2 laser therapy [7].…”
Section: Co 2 Lasermentioning
confidence: 99%